ANALISIS PENENTUAN MUTU AIR BEBERAPA SUNGAI DI JAWA TENGAH DENGAN METODE STORET DAN INDEKS PENCEMARAN - Huboyo, Haryono Setiyo; Nugraha, Winardi Dwi; Indah, Rahmah (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2009)
There  are  some  river  basin  in  Central  Java,  such  as  Gung  River  Basin, Serayu  River  Basin  and Garang River Basin. Many sector that are dependable on the river resources, while on the hand the quality of the river is decreasing because of the waste water pollutant produced by many human or industrial activities. Therefore, proposal study of water class determination can be done by 2 methods according  to  Environmental  Ministry  Decision  No.  115  year  2003 about  Water  Quality  Status Determination Handbook, which are STORET and Pollution Index (PI). Using those two methods will be determined the real water class through comparison between water quality parameter with defined standard according to PP No. 82 year 2001. The usage of these 2 methods often resulting in different output, because of the difference of equal weight from each parameter and the existence constanta of P at Pollution Index (PI) which not clear relevancy.